2020
DOI: 10.1016/j.clon.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Re-irradiation With Single-modality Interstitial Brachytherapy for the Treatment of Recurrent Gynaecological Tumours in the Pelvis: A Multi-institutional Study

Abstract: Aims: Recurrent gynaecological tumours can cause significant morbidity with limited salvage options. This study investigates the strategy of salvage singlemodality interstitial brachytherapy (SM-ISBT) for recurrent gynaecological pelvic cancer at two specialised ISBT centres. Materials and methods: Patients who had received salvage SM-ISBT for pelvic recurrence of gynaecological cancers from September 2008 to January 2017 were included. None had distant metastasis at the time of recurrence. Local control, prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Over the past 20 years, 14 retrospectives series, and one phase II prospective study with only few patients [31], reported clinical experiences of high dose rate (HDR) or low dose rate (LDR) 3D-IGBT in previously irradiated pelvic recurrences of gynecologic malignancies (Table 1) [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. In nine of those, 100% of the population received prior BT, prior EBRT, or a combination of EBRT followed with BT [31][32][33]36,40,41,[43][44][45]. In the six remaining articles, only a variable subset of patients (from 10% to 85.7% of the studied population) received IGBT in a re-irradiation setting [34,35,[37][38][39]42].…”
Section: General Aspectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past 20 years, 14 retrospectives series, and one phase II prospective study with only few patients [31], reported clinical experiences of high dose rate (HDR) or low dose rate (LDR) 3D-IGBT in previously irradiated pelvic recurrences of gynecologic malignancies (Table 1) [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. In nine of those, 100% of the population received prior BT, prior EBRT, or a combination of EBRT followed with BT [31][32][33]36,40,41,[43][44][45]. In the six remaining articles, only a variable subset of patients (from 10% to 85.7% of the studied population) received IGBT in a re-irradiation setting [34,35,[37][38][39]42].…”
Section: General Aspectsmentioning
confidence: 99%
“…The vast majority of the studies focused on isolated local recurrences, occurring in the vagina, paravaginal, pelvic sidewall, cervix (if hysterectomy was not performed as a part of the initial treatment), vulva or sub-urethra [31][32][33][34][35][36][37][38][39][40][41][42][43]45]. In only one study, regional and distant metastasis were not excluded, and occurred simultaneously to local relapse in four patients (two patients (9.1%) with nodal involvement and two patients (9.1%) with distant oligometastasis) [44].…”
Section: Type Of Recurrencementioning
confidence: 99%
See 3 more Smart Citations